Acute abdominal picture determined by primary pathology of the greater omentum - González, Daniel; Vega, Alvaro; Monti, José; Torres, Marcos; di Leoni, Francisco (Cirugía del Uruguay, 2006)
Primary pathology of greater epiploon is characterized by its low incidence. It may occur in all age groups, with a certain predominance in the male sex. Its onset is characterized by acute abdominal pain and notwithstanding some image signs that may contribute towards its diagnosis, the latter is rarely established. Confirmation is during surgical exploration and its treatment is omentectomy adapted to involved tissue extension in benign processes Total exeresis is reserved for malignant cases.